Seals of Kommerkiarioi of the Ros’ - Elena Vladimirovna Stepanova (Античная древность и средние века)
This article addresses the seals of the kommerkiarioi of the Ros’. So far there are known two groups of the seals in question. The first includes five specimens showing the flowering patriarchal cross on two steps on the obverse and the Greek inscription “Seal of the kommerkiarioi of the Ros’” on the reverse. The find-spots of most specimens are known: one artefact was discovered in Rybinsk at the Rus’ian settlement of Ust’-Sheksna, and three at the territory of Veliky Novgorod. The fifth piece resides in the State Hermitage Museum collection: it was acquired from the antiquary Osman Nuri-Bey in the early-twentieth century; its provenance is not known. These seals date from the late-eleventh to early-twelfth century. The second group of the seals comprises four specimens. There is metric inscription on both sides: “I am a seal of the kommerkion of the Ros’”. These seals were found in the town of Mena, Chernihiv oblast’ (Ukraine); in Belarus; in Ukraine; in the village of Hlyboke (Boryspil’ district, Kiev oblast’). W. Seibt dates them to the second or third thirty years of the twelfth century. These lead seals are of interest in many ways. The ethnonym Ῥῶς occurs on Byzantine seals for the first time. No less interesting is the mention of the kommerkiarioi of the Ros’ in one case and the kommerkion of the Ros’ in the other. The kommerkiarioi, or collectors of custom duties, are known as long as the late-twelfth century. The kommerkion is a set of the trade duties imposed by the state, usually amounting to 10% of the goods value. In both cases, it is the case of the Byzantine customs working with trade with Rus’ian towns in the late-eleventh and twelfth century.